Killing fear a novel of suspense - Brennan, Allison (New York Ballantine Books, 2008)
When Theodore Glenn escapes from prison, he continues the murdering spree ended by his incarceration seven years ago, but this time his target is the woman who put him behind bars--ex-stripper and club owner Robin McKenna.
Includes an excerpt from: Tempting evil (p. [422]-429).
Series from authors website.
91835
Keywords: Serial murderers; Romantic suspense fiction; Suspense fiction